TINJAUAN PERLINDUNGAN KARAKTER FIKSI MELALUI MEREK BERDASARKAN STUDY KASUS SENGKETA MEREK SUPER MARIO BROSi - Sri Arlina; Radian Suparba; Teguh Rama Prasja (JOURNAL EQUITABLE, 2022)
The case of a fictional character who became a trademarks is the case of the "Super Mario Bros" trademarks in which individual trademarks holders, Indonesian companies and the Director General of Intellectual Property were sued by a well-known game company, Nintendo. The crew of 'mario bros' characters were used as packaging designs and characters in the game, but because the game has been loved by people in countries such as Australia, Malaysia, India, China, including Indonesia in the 90s (nineties), Nintendo decided to register the character. "super mario bros" and its variants use trademark registration media. This means that the Nintendo company avoids legal turmoil caused by irresponsible parties to use fictional characters have sold tens of thousands of copies.However, even though it has been registered, there are still parties who have managed to get the rights to the brand with the "Super Mario Bros" logo. Registered in 1994 in the name of an individual or individual before being transferred to a legal entity or company.